MeTayutay: An E-Learning Instructional Tool on Figures of Speech in Selected Short Stories by Genoveva Edroza-Matute - Amarillento, Clarence Angelo J.; Lanuza, France Elaen M.; Sunio, Ian Jay C. (Journal of Education Method and Learning Strategy, 2025)
This study evaluates the effectiveness of MeTayutay, an e-learning tool designed to teach figures of speech and examines the figures of speech found in selected works of Genoveva Edroza-Matute as supplementary learning material. It is grounded in the TPACK Framework (Mishra & Koehler), Connectivism Learning Theory (Siemens & Downes), Formalist Theory, and Reader’s Response Theory. Analysis identified metaphor, paradox, hyperbole, synecdoche, metonymy, simile, rhetorical question, personification, and euphemism in Matute’s works, with metaphor being the most frequently used. These works serve as valuable resources for teaching figurative language. Additionally, MeTayutay proves to be an effective digital instructional tool for improving students’ understanding of figures of speech, reinforcing their learning through interactive and supplementary content.